EKSPLORASI MANIFESTASI MORALITAS PESERTA DIDIK DALAM PEMBELAJARAN SENI TARI DAN SENI SUARA BERBASIS PROYEK KOLABORATIF: Studi Deskriptif Kualitatif di SMA Kristen Anak Panah Nabire - Widjaja, Hana Sumiati; Hartono; Rokhman, Fathur; Wagiran (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This qualitative descriptive study explores the manifestations of student morality in collaborative project-based learning in dance and vocal arts education at SMA Kristen Anak Panah Nabire, Indonesia. This research aims to investigate how aesthetic experiences and collaborative artistic activities contribute to the internalization and expression of moral values. Data collection was conducted through participant observation, in-depth interviews, and documentation analysis during the "Warisan Budaya Nusantara" (Nusantara Cultural Heritage) collaborative art project, with 64 students and 2 art teachers as participants. Data were collected through classroom observations, reflective journals, and semi-structured interviews with students and teachers. The analysis results show four main manifestations of morality: (1) the growth of personal and collective responsibility in group commitments; (2) the development of empathy and social awareness during the rehearsal process; (3) the strengthening of cooperation and solidarity in resolving conflicts and achieving artistic goals; and (4) the emergence of moral reflection through aesthetic experiences. These findings indicate that moral values are not only transmitted cognitively but are also experienced through social interaction, emotional experiences, and shared reflection within a contextual creative process. The implications highlight that project-based learning in arts education can function as a moral ecology—an environment where artistic collaboration becomes a living process of ethical formation. This study contributes to the theoretical discourse on art and morality, and provides practical recommendations for teachers and curriculum designers to foster character development through arts education.